2013
DOI: 10.1371/journal.pone.0072659
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Pre-Clinical Studies of Early Decompression in Acute Spinal Cord Injury: A Battle of Time and Pressure

Abstract: BackgroundThe use of early decompression in the management of acute spinal cord injury (SCI) remains contentious despite many pre-clinical studies demonstrating benefits and a small number of supportive clinical studies. Although the pre-clinical literature favours the concept of early decompression, translation is hindered by uncertainties regarding overall treatment efficacy and timing of decompression.MethodsWe performed meta-analysis to examine the pre-clinical literature on acute decompression of the inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 69 publications
(49 reference statements)
2
62
0
2
Order By: Relevance
“…Because damage in the primary phase cannot be prevented, all approaches focus on restricting damage in the secondary phase of the injury. Some animal models have suggested that surgical decompression of the spinal cord is accompanied by a reduction of secondary damage, as well as an improvement in motor function 9. Clear evidence for a positive neuroprotective effect of spinal cord decompression and improved clinical outcome is still absent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because damage in the primary phase cannot be prevented, all approaches focus on restricting damage in the secondary phase of the injury. Some animal models have suggested that surgical decompression of the spinal cord is accompanied by a reduction of secondary damage, as well as an improvement in motor function 9. Clear evidence for a positive neuroprotective effect of spinal cord decompression and improved clinical outcome is still absent.…”
Section: Introductionmentioning
confidence: 99%
“…Clear evidence for a positive neuroprotective effect of spinal cord decompression and improved clinical outcome is still absent. Also, the proper timing for decompression remains controversial; however, most studies indicate an enhanced neuroprotective effect after early spinal cord decompression 912…”
Section: Introductionmentioning
confidence: 99%
“…58 In the absence of prior injury, brief periods (seconds-minutes) of moderate cord compression are relatively well tolerated 59,60 whereas, with pre-existing cord injury/compression, the amount and duration of “tolerable” compression is likely to be much less. 61 Consequently, our general conclusion regarding the clinical utility/safety of either the Macintosh or Airtraq in the setting of a Type II odontoid fracture may not apply in the setting of pre-existing bony displacement and/or cervical cord injury.…”
Section: Discussionmentioning
confidence: 91%
“…Preclinical studies show patterns of primary and secondary injury mechanisms and provide reasoning toward surgical decompression (7). For one, many of these core concepts have been the basis of care of patients with spinal cord injuries (SCIs).…”
mentioning
confidence: 99%